2014
DOI: 10.1186/1744-8069-10-40
|View full text |Cite
|
Sign up to set email alerts
|

Roles of ASIC3, TRPV1, and NaV1.8 in the Transition from Acute to Chronic Pain in a Mouse Model of Fibromyalgia

Abstract: BackgroundTissue acidosis is effective in causing chronic muscle pain. However, how muscle nociceptors contribute to the transition from acute to chronic pain is largely unknown.ResultsHere we showed that a single intramuscular acid injection induced a priming effect on muscle nociceptors of mice. The primed muscle nociceptors were plastic and permitted the development of long-lasting chronic hyperalgesia induced by a second acid insult. The plastic changes of muscle nociceptors were modality-specific and requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(95 citation statements)
references
References 57 publications
5
89
0
Order By: Relevance
“…Previous studies report that activating TRPV1 inhibits TTX-R current in primary sensory neurons, which may account for the analgesia of capsaicin [29,30]. However, the increased TRPV1 and TTX-R current is required for developing chronic hyperalgesia [31]. In the future study, more experiments are required to clarify whether the increased α-subunit expression upon the chronic TRPV4 activation will lead to an increased of I Na .…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies report that activating TRPV1 inhibits TTX-R current in primary sensory neurons, which may account for the analgesia of capsaicin [29,30]. However, the increased TRPV1 and TTX-R current is required for developing chronic hyperalgesia [31]. In the future study, more experiments are required to clarify whether the increased α-subunit expression upon the chronic TRPV4 activation will lead to an increased of I Na .…”
Section: Discussionmentioning
confidence: 95%
“…A recent study has shown the importance of a trio of TRP receptors (TRPM3, TRPV1, and TRPA1) that are functionally redundant TRP channels, representing a fault‐tolerant mechanism to avoid burn injury . Little is known about these receptors in FM, but preclinical and clinical studies have shown that certain TRPV haplotypes contribute to the symptoms of FM . QST findings in FM reveal an alarm system to thermal insults that is amplified and prioritized compared to discriminative information.…”
Section: Discussionmentioning
confidence: 99%
“…ASIC3−/− mice do not develop hyperalgesia after repeated acid injections into muscle, inflammation of muscle, or inflammation of joint [2729, 4447]. Further, prior studies also show that blockade of ASICs locally in muscle both prevents and reverses muscle hyperalgesia associated with either repeated acid injections into muscle or muscle inflammation [29, 47, 48]. The current study is consistent with these prior studies and shows that fatigue-enhanced hyperalgesia does not occur in ASIC3−/− mice or after pharmacological blockade of ASIC3 in muscle.…”
Section: Discussionmentioning
confidence: 99%